Determination of Sulphurdioxide (SO2) Distribution in the Eastern Black Sea Region with Geographical Information System - Kazım Onur Demirarslan; Halil Akıncı (Doğal Afetler ve Çevre Dergisi)
Air pollution occurs more particularly in areas where there are an intense and unplanned urbanization. Because of the pollution, air quality is reduced and the pollution causes the various health problems. In this study, sulphurdioxide (SO2) concentration distributions has been examined in The Eastern Black Sea region where decreasing air quality because of the non-planned urbanization and topographical reasons. Fossil fuels used for heating especially in the winter season lead to air pollution dramatically. The Black Sea Coast could be one of the major sources of the air pollution in the study area. In this study, the effects and distributions of SO2 polluter on air quality is investigated by produced maps with the help of geographical information systems in the area of Eastern Black Sea zone that has Artvin, Bayburt, Giresun, Gumushane, Ordu, Rize, and Trabzon cities.The related data of air quality, measurement stations which are belonging to The Ministry of Environment and Urbanization, have been used to measure hourly data between 2011-2016 years. The outcomes of this study, the means of SO2 concentrations ranking is found in spring seasons, Ordu > Giresun > Trabzon > Gumushane > Rize > Bayburt > Artvin, in summer seasons, Trabzon > Giresun > Rize > Ordu > Artvin > Bayburt, in fall seasons, Trabzon > Ordu > Gumushane > Giresun > Bayburt > Artvin > Rize, in winter seasons, Ordu > Trabzon > Gumushane > Giresun > Bayburt > Artvin > Rize.